2018
DOI: 10.1155/2018/8694579
|View full text |Cite
|
Sign up to set email alerts
|

Revising Reverse-Phase Chromatographic Behavior for Efficient Differentiation of Both Positional and Geometrical Isomers of Dicaffeoylquinic Acids

Abstract: Dicaffeoylquinic acids (diCQAs) are plant metabolites and undergo trans-cis-isomerization when exposed to UV irradiation. As such, diCQAs exist in both trans-and cis-configurations and amplify the already complex plant metabolome. However, analytical differentiation of these geometrical isomers using mass spectrometry (MS) approaches has proven to be extremely challenging. Exploring the chromatographic space to develop possible conditions that would aid in differentially separating and determining the elution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Differences observed in the intensities of fragment ions can be ascribed to variances in energy distribution which cause the structurally similar isomers to behave differently under the described MS conditions. On a reverse-phase column the elution order of di-CQA regio-isomers is expected to be as follows: 3,4-di-CQA, 3,5-di-CQA, followed by 4,5-di-CQA eluting the latest, validating the annotation of di-CQAs shown in Table 1 [21,29]. These di-CQA were differentially present throughout tissues and cell cultures of B. pilosa.…”
Section: Characterization Of Di-caffeoylquinic Acids (Di-cqas)mentioning
confidence: 53%
See 2 more Smart Citations
“…Differences observed in the intensities of fragment ions can be ascribed to variances in energy distribution which cause the structurally similar isomers to behave differently under the described MS conditions. On a reverse-phase column the elution order of di-CQA regio-isomers is expected to be as follows: 3,4-di-CQA, 3,5-di-CQA, followed by 4,5-di-CQA eluting the latest, validating the annotation of di-CQAs shown in Table 1 [21,29]. These di-CQA were differentially present throughout tissues and cell cultures of B. pilosa.…”
Section: Characterization Of Di-caffeoylquinic Acids (Di-cqas)mentioning
confidence: 53%
“…Metabolite (10) was identified as CA (Figure S7B) by its molecular ion [M-H] -, at m/z 473 which fragmented to give product ions at m/z 311 [CTA-H]due to the loss of a second caffeic acid residue. Other daughter ions at m/z 149 [TA-H]and m/z 135 [CFA-CO 2 ]were also observed [29]. Profiling of the tartaric esters revealed that they are only present in the aerial parts of the plants and absent in the roots.…”
Section: Characterization Of Hydroxycinnamoyl-tartaric Acid Estersmentioning
confidence: 98%
See 1 more Smart Citation
“…Plants produce a myriad of organic compounds referred to as secondary metabolites (natural products) which differ in their structure and biosynthetic origins. These metabolites undergo chemical modifications, such as conjugation [ 1 , 2 ], and isomerization (positional and geometrical) [ 3 6 ], which further contribute to the high complexity of the plant metabolome. For instance, secondary metabolites such as hydroxycinnamic acid (HCA) derivatives have the potential to form conjugates with organic acids such as isocitric acid [ 1 ], tartaric acid [ 2 , 7 9 ], and quinic acid [ 4 , 10 , 11 ], thus forming hydroxycinnamoyl-isocitric acid [ 1 ], hydroxycinnamoyl-tartaric acid [ 2 , 7 9 ], and hydroxycinnamoyl-quinic acid [ 4 , 10 , 11 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these HCA derivatives undergo isomerization to produce positional isomers such as di-acylated hydroxycinnamoyl-quinic acid derivatives like 1,3-dicaffeoylquinic acid (1,3-diCQA) or 1,5-diCQA [ 3 6 ]. As such, some HCA conjugates have been found to result in isobaric compounds which produce similar mass spectrometry (MS) fragmentation patterns [ 1 ], and this renders identification challenging from an analytical perspective.…”
Section: Introductionmentioning
confidence: 99%